Digital Design and Research of Reliability Allocation of the Gear Transmission System - Han Yingying; Ai Hongxu; Shen Qiang; Li Ziyuan; Li Wei (Jixie chuandong)
With the development of the gear transmission system towards complexity, multiple transmission types and high reliability, it becomes more and more important to assign the reliability of the gear transmission system quickly and accurately. In this study, aiming at the problems of incomplete consideration factors, inconsistent range of changes in different allocation methods for the same parameter, and inconvenient digital software development in existing reliability allocation methods, an improved advisory group on reliability of electronic equipment (AGREE) allocation method is proposed, the scoring allocation method is extended, and the digital characteristics of reliability allocation method are discussed. The basic reliability model and task reliability model of the complex gear transmission system are established, and the traversal algorithm of the automatic reliability model generation is studied. A digital platform for rapid reliability allocation of fixed axle gear train, planetary gear train and hybrid gear train is developed. Four independent modules, namely input module, calculation module, result display module and output module, are designed. The accuracy of the calculation results of the software is verified by comparing with the results of examples. The parametric modeling and the automatic generation of the example report for the reliability allocation of the gear transmission system are realized, and the accuracy and efficiency of the reliability allocation model are raised.